A Unified Latent Variable Model for Contrastive Opinion Mining - Ibeke, Ebuka; Lin, Chenghua; Wyner, Adam; Mohamad Hardyman, Barawi (Higher Education Press and Springer-Verlag GmbH Germany, 2017)
Ebuka IBEKE, Chenghua LIN , Adam WYNER, Mohamad Hardyman BARAWI